Comparison of primary human gingival fibroblasts from an older and a young donor on the evaluation of cytotoxicity of denture adhesives - Aline S. L. Santoro Soares; Miriam Zaccaro Scelza; Janaína Spoladore; Marcos Antônio Gallito; Felipe Oliveira; Rita de Cássia Martins Moraes; Gutemberg Gomes Alves (University of São Paulo, 2018)
Abstract Denture adhesives (DA) improve the retention and stability of ill-fitting dentures, especially for older adults. These materials should be biocompatible, i.e., they cannot cause undesired biological responses and be non-cytotoxic to oral tissues. However, in vitro testing of DA biocompatibility employing primary cell culture may possibly be affected by other factors, such as the donor age. Objective To compare the cytotoxicity of three different denture adhesives when assessed in primary gingival fibroblasts from a young donor or from an older donor, as well as the release of the basic fibroblast growth factor (bFGF), and the inflammatory response marker interleukin-6 (IL-6). Material and Methods Gingival fibroblasts isolated from a 30- and a 62-year-old donor were assayed for proliferation (1-7 days) and sensitivity to latex (positive control). Fibroblasts were indirectly exposed to Corega Ultra (cream), Corega powder and Fixodent Original for a 24 h period and assayed by XTT and Crystal Violet tests. The release of IL-6 and bFGF by exposed cells was determined by ELISA. Results While cells from the young donor presented higher cell growth after 7 days, the sensitivity to increasing concentrations of latex extracts was very similar between young and older cells. Both XTT and CVDE detected no difference between the DA and the control group. All materials induced higher levels of IL-6 and bFGF compared to control. Cells from the older donor exposed to Corega Ultra released lower levels of cytokine and growth factor. Conclusions All materials were considered non-cytotoxic, but affected cytokine and growth factor release. The biological differences found between fibroblasts from both donors could be due to individual or age-related factors. The authors suggest the use of cells from older donors on studies of dental products aimed at older patients, to better simulate their physiological response.